The Impact of Green Marketing and Employee Well-being Training Programs on Employee Retention and Customer Satisfaction in Indonesia - Heri Setiyawan; Mohammad Gifari Sono; Aria Elshifa (Westscience Press, 2026)
The growing emphasis on sustainability and employee development has encouraged organizations to adopt environmentally responsible marketing strategies and employee welfare initiatives to enhance organizational performance. This study examines the impact of Eco-Friendly Marketing and Employee Welfare Training Programs on Employee Retention and Customer Satisfaction in Indonesia. A quantitative research approach was employed using data collected from 175 respondents through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that Eco-Friendly Marketing has a positive and significant effect on Employee Retention and Customer Satisfaction. Employee Welfare Training Programs also demonstrate positive and significant effects on Employee Retention and Customer Satisfaction. Furthermore, Employee Retention significantly influences Customer Satisfaction. The structural model explains 68.3% of the variance in Employee Retention and 78.1% of the variance in Customer Satisfaction, indicating strong predictive capability. The findings suggest that organizations implementing sustainable marketing practices alongside employee welfare development programs are more likely to retain employees and achieve higher levels of customer satisfaction. This study contributes to the literature on sustainability and human resource management by demonstrating the interconnected role of environmental responsibility and employee-focused initiatives in enhancing organizational performance within the Indonesian context.